An Anthropological Study on the Health Seeking Behavior of Tomboy, Bakla, and Minamagkit From Mountain Province, Northern Philippines - Josef, Jennifer Curry (Review of Women's Studies; Vol 32 No 1 (2022): Review of Women's Studies Volume XXXII, Number 1 (2022), 2023)
This paper explores the health situation and health seeking behavior of tomboys, bakla, and minamagkit from Mountain Province. Minamagkit can be translated as "like a lady" referring to a person whose biological sex at birth is male, but whose gender identity and expression is female. The research objective is to document and analyze the general health situation of these groups and their sexual and reproductive health seeking behavior, using a gender and culturally sensitive approach. The research also employed the analytical lenses of intersectionality, critical medical anthropology, and ethnomedicine. Using intersectionality, the health situation and health seeking behavior of the tomboys, bakla, and minamagkit were analyzed taking into consideration the various dimensions of their identity such as gender, sexuality, ethnicity, indigeneity, socioeconomic class, geographic location, culture, etc. The analytical framework of critical anthropology and ethnomedicine, i.e., using Western biomedicine, popular and folk medicine, were employed to arrive at a more nuanced understanding of the health seeking behavior. Like the general population in Tadian, Bontoc, and Sagada, the minamagkit, bakla, and tomboy key informants commonly rely on the popular and folk sectors of ethnomedicine. The popular sector includes strategies employed by the family and other significant social networks which are not part of the medical profession. The folk sector includes strategies employed by "nonprofessional" indigenous healers. Results suggest that the socio-economic status, gender/sexual identity, indigeneity and geographic location of residence, and the general situation of the health infrastructure in the Philippines and Cordillera significantly impact on the poor health situation and health seeking behavior of the tomboys, bakla, and minamagkit. The project consists of two parts. The first phase is the research on the health and well-being of the tomboy, bakla, and minamagkit. The second phase consists of sexual and reproductive health seminars, and providing medical tests related to cardiovascular, respiratory, sexual, and reproductive health.